PERAN PG-PAUD UHAMKA DALAM PENDAMPINGAN KOMUNITAS MATAHARI KECIL DALAM MENINGKATKAN KUALITAS PENDIDIKAN ANAK USIA DINI - Silvie Mil; Anita Dewi Ekawati (Universitas Negeri Semarang, 2018)
To serve a good education is not only become government responsibility, but also higher education institutions that produce human resources such us teachers and it also become society’s responsibilities. In order the quality of early childhood education, a partnership is needed which in this case involves the University of Muhammadiyah Prof. Dr. Hamka, Matahari Kecil as a non-governmental organization and private kindergarten Warga Teladan. This was realized through the holding of the Community Partnership Program